Customized platelet-rich plasma with transforming growth factor β1 neutralization antibody to reduce fibrosis in skeletal muscle. (May 2016) - Li, Hongshuai; Hicks, Justin J.; Wang, Ling; Oyster, Nick; Philippon, Marc J.; Hurwitz, Shepard; Hogan, MaCalus V.; Huard, Johnny
Abstract: The formation of fibrous tissue during the healing of skeletal muscle injuries leads to incomplete recovery of the injured muscle. Platelet-rich-plasma (PRP) contains beneficial growth factors for skeletal muscle repair; however, it also contains deleterious cytokines and growth factors, such as TGF-β1, that can cause fibrosis and inhibit optimal muscle healing. Objective: To test if neutralizing TGF-β1's action within PRP, through neutralization antibodies, could improve PRP's beneficial effect on skeletal muscle repair. Methods: PRP was isolated from in-bred Fisher rats. TGF-β1 neutralization antibody (Ab) was used to block the TGF-β1 within the PRP prior to injection. The effects of customized PRP (TGF-β1 neutralized PRP) on muscle healing was tested on a cardiotoxin (CTX) induced muscle injury model. Results: A significant increase in the numbers of regenerative myofibers was observed in the PRP and customized PRP groups compared to the untreated control. A significant decrease in collagen deposition was observed in customized PRP groups when compared to the control and PRP groups. Significantly enhanced angiogenesis and more Pax-7 positive satellite cells were found in the PRP and customized PRP groups compared to the control group. Macrophage infiltration was increased in the customized PRP groups when compared with the PRP group. More M2 macrophages were recruited to the injury site in the customized PRP groups when compared with the PRP and control groups. Conclusion: Neutralizing TGF-β1 within PRP significantly promotes muscle regeneration while significantly reducing fibrosis. Not only did the neutralization reduce fibrosis, it enhanced angiogenesis, prolonged satellite cell activation, and recruited a greater number of M2 macrophages to the injury site which also contributed to the efficacy that the customized PRP had on muscle healing.